2022
DOI: 10.1089/g4h.2021.0207
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in a Physical Activity App: What Gamification Features Are Being Used, by Whom, and Does It Make a Difference?

Abstract: Background: Gamification is purported to enhance engagement with health behavior apps, ultimately improving their effectiveness. This study aimed to examine (1) whether the inclusion of gamification features in a physical activity smartphone app was associated with improved app usage and goal adherence, describe (2) use of the gamification features, and (3) by whom, and determine (4) whether engagement was associated with increased physical activity. Methods: Data from community-dwelling adult participants (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Whether in a global way the literature on gamification shows cautiously positive results in the use of gamification for older people, 31 the present results are in line with a previous study 32 which found that older users had a greater degree of use of the gamification features. The authors proposed the explanation that older adults pay generally more attention to their health and thus have a stronger intention to engage in a health program.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Whether in a global way the literature on gamification shows cautiously positive results in the use of gamification for older people, 31 the present results are in line with a previous study 32 which found that older users had a greater degree of use of the gamification features. The authors proposed the explanation that older adults pay generally more attention to their health and thus have a stronger intention to engage in a health program.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with previous findings demonstrating that higher use of gamification features was associated with greater intervention effectiveness. 32,34 If gamification can ultimately increase program engagement, developers need first to design their apps to be as attractive as possible and optimize retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the gamified features in the child app (e.g., getting coins, virtual adventure trail, family leaderboard) were well-received by the children, and this promoted their engagement with the activity tracker and app. This aligns with many technology-based physical activity interventions’ [ 42 , 48 , 49 , 50 ] showing that social comparison and gamification embedded in activity trackers and apps enhances participants’ intervention engagement. In turn, high intervention engagement is known to positively influence interventions’ effects on physical activity [ 51 ].…”
Section: Discussionsupporting
confidence: 82%
“…When comparing the results with those of research in adults, several features are shared, such as a simple and structured interface, tailored and positive feedback on PA levels [ 43 , 44 , 89 , 90 ], progress [ 90 ], well-designed reminders (eg, timing and frequency of notifications) [ 26 , 43 , 44 , 89 ], rewards [ 43 , 44 , 49 , 91 - 93 ], self-monitoring [ 26 , 43 , 44 ], goal-setting, [ 43 , 44 ], clear navigation [ 43 , 44 ], accurate tracking function [ 43 ], personalization (eg, goals) [ 94 ], and the offer of a variety of features [ 43 , 95 ]. Technical difficulties were also negatively influencing engagement in adults [ 43 , 89 ].…”
Section: Discussionmentioning
confidence: 99%